1993
DOI: 10.1104/pp.101.4.1305
|View full text |Cite
|
Sign up to set email alerts
|

Water Transport in Onion (Allium cepa L.) Roots (Changes of Axial and Radial Hydraulic Conductivities during Root Development)

Abstract: The hydraulic architecture of developing onion (Allium cepa L. cv Calypso) roots grown hydroponically was determined by measuring axial and radial hydraulic conductivities (equal to inverse of specific hydraulic resistances). In the roots, Casparian bands and suberin lamellae develop in the endodermis and exodermis (equal to hypodermis). Using the root pressure probe, changes of hydraulic conductivities along the developing roots were analyzed with high resolution. Axial hydraulic conductivity (L,) was also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 34 publications
0
51
0
2
Order By: Relevance
“…For instance, suberization of apoplastic barriers has classically been associated with root maturation and reduced water uptake capacity (Melchior and Steudle, 1993;Zimmermann and Steudle, 1998). Although Arabidopsis accessions showed significant variation in their root anatomy, we did not observe any clear link between root suberization and the hydraulic conductivity of the aquaporin-independent path.…”
Section: Molecular and Cellular Bases Of Root Water Transportmentioning
confidence: 44%
See 1 more Smart Citation
“…For instance, suberization of apoplastic barriers has classically been associated with root maturation and reduced water uptake capacity (Melchior and Steudle, 1993;Zimmermann and Steudle, 1998). Although Arabidopsis accessions showed significant variation in their root anatomy, we did not observe any clear link between root suberization and the hydraulic conductivity of the aquaporin-independent path.…”
Section: Molecular and Cellular Bases Of Root Water Transportmentioning
confidence: 44%
“…Water transport across living tissues can also involve the apoplast (Steudle and Peterson, 1998), although the molecular bases and genetic control of this path are somewhat less understood. Yet, it was recently shown that suberin deposition in specialized root cell layers (exodermis and endodermis), which may affect root water transport properties, can vary between genotypes (Baxter et al, 2009) and physiological contexts (Melchior and Steudle, 1993;Zimmermann et al, 2000;Vandeleur et al, 2009). In addition, fully differentiated xylem vessels usually provide, with respect to radial hydraulic conductance, a nonlimiting axial conductance.…”
mentioning
confidence: 99%
“…One can observe that stem resistance also contributes to the overall resistance of the canopyatmosphere system. However, in resistance studies by Melchior and Steudle (1993), it was found that resistance to water flow was usually negligible where the xylem had already matured.…”
Section: Stomatal Resistancementioning
confidence: 99%
“…Thornley and Johnson (1990) explained how the resistance from root surface to the plant vary with the number of roots per unit area in a vertically-structured soil profile. Melchior and Steudle (1993) stated that R l can contribute substantially to the overall hydraulic resistance or even can be the limiting component. Passioura (1972), Newman (1976) and Meyer and Ritchie (1980) used a modified Poiseuille-Hagen equation to calculate R l from root xylem dimensions:…”
Section: Water Flow Resistances In the Soil-root Systemmentioning
confidence: 99%
“…3) of pressure relaxations. The use of a proper value of PE had some impact on the evaluation of k, , (TsI2"') (Birner and Steudle, 1993;Melchior and Steudle, 1993).…”
Section: P and Lpmentioning
confidence: 99%